Passing. Anatomies and Physiologies of Identity Transformations - MUDURE, Mihaela; NANDA, Aparajita (Presa Universitară Clujeană, 2024)
As an identity shift that has existed for centuries, passing is a strategy to change one’s perceived identity that cannot be separated from colorism, or the preference for individuals exhibiting European-like bodily features. The results of the psychological study of colorism undertaken by Crutchfield et al. show that this predilection is a “historical trauma response [that] not only incorporates subjugation of oppressed African Americans, but can also incorporate resistance” (826). Passing can send mixed messages where oppression contaminates resistance and vice versa.